Peningkatan Pengetahuan dan Kepatuhan Pasien Hipertensi melalui Edukasi Self-Management di Puskesmas Aifat, Kabupaten Maybrat - Sinar Aisyah; Prima Dewi Kusumawati (Yayasan Inspirasi El Burhani, 2026)
Introduction: Hypertension remains one of the leading non-communicable diseases requiring lifelong treatment. However, low medication adherence and limited patient understanding of hypertension management continue to hinder successful blood pressure control, particularly in primary healthcare settings. Community-based health education emphasizing self-management is considered an effective strategy to improve patients' knowledge and adherence to treatment. Objective: The purpose of this service was to improve the knowledge and medication adherence of patients with hypertension through a self-management education program implemented at the Aifat Primary Health Center, Maybrat Regency. Method: This public service was conducted using a participatory educational approach based on a structured health education plan. Thirty patients with hypertension participated in the program, which included blood pressure screening, pre-test assessment, interactive health education, group discussion, demonstration of the PAGAR-AIFAT Standard Operating Procedure, distribution of educational leaflets, family involvement, and post-test evaluation to assess changes in participants' knowledge and treatment adherence. Result: The evaluation showed an improvement in participants’ knowledge and medication adherence after the intervention. The proportion of participants with good knowledge increased to 60.0%, while high medication adherence reached 56.7% after the education program. The implementation of the PAGAR-AIFAT approach and educational leaflets provided practical tools to support continuous medication management and hypertension self-care. Conclusion: Self-management education combined with family involvement and the implementation of the PAGAR-AIFAT approach effectively enhanced patients' knowledge and medication adherence. This community service program can serve as a practical and sustainable educational model to strengthen hypertension management in primary healthcare services.